Peran Kode Etik Untuk Meningkatkan Profesionalisme Guru Pendidikan Agama Kristen - Dosmaria Panjaitan; Dorlan Naibaho (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The code of ethics for Christian Religious Education (PAK) teachers plays an important role in increasing teacher professionalism in Indonesia. In the educational context, professionalism does not only include teaching skills, but also the moral and ethical attitudes that must be applied in carrying out their duties. Codes of ethics provide guidelines for teachers to act in accordance with established standards, which include responsibilities towards students, society and educational institutions. This research aims to analyze how the application of a code of ethics in the practice of Christian religious education can contribute to the development of teacher professionalism, as well as its impact on the quality of learning and the formation of student character. Based on a literature review, it was found that consistent application of a code of ethics helps teachers to maintain their integrity, improve relationships with students, and set a good example in everyday life. Therefore, increasing understanding and implementing a good code of ethics is very necessary to realize quality education that is beneficial for students' spiritual and moral development.